The Constitutional law and judicial education - Domínguez Haro, Helder (2021)
This paper shows the evolution of the teaching of constitutional law (and constitutional procedural law) in the procedures for the education of judges over the last five decades carried out by the Judiciary and the Academy of the Judiciary. From a critical reflection and analysis, the author identifies the treatment that courses on constitutional law have deserved in each decade, along with the stages of the teaching of this discipline in the academic sphere. He warns that judicial training on constitutional issues - in a general sense - has not been as regular as expected, despite the efforts that this implies on the part of the agencies committed to enhancing the capacities of magistrates. It also emphasizes the need to generate what has come to be called «constitutional sentiment» in the professional training of judges, which involves the challenge of assuming public training policies by our times.